Optimization Of Patient Flow Management To Reduce Waiting Time In Outpatient Services: A Study In A Type B Hospital In Jakarta - Wahyu Purnama; Siswanto Pabidang (CV. AFDIFAL MAJU BERKAH, 2026)
Patient waiting time is an important indicator of hospital service quality and significantly affects patient satisfaction as well as operational efficiency. To analyze factors contributing to prolonged waiting times and to evaluate patient flow management interventions in outpatient services. This was a quasi-experimental study using a pre–post intervention design. Data were collected over three months before and after the intervention, which included the implementation of an electronic registration system, time-based scheduling, and redistribution of medical staff. The average waiting time decreased from 120 ± 30 minutes to 65 ± 20 minutes (p < 0.001). Patient satisfaction increased from 68% to 85%. The main contributing factors were physician delays, registration bottlenecks, and imbalance in patient load distribution. Patient flow management-based interventions significantly reduced waiting time and improved patient satisfaction. Continuous implementation and routine monitoring are required.